Teachers’ Competency on the Use of ICT in Teaching Physics in the Junior High School - Briones, C B (KnE Social Sciences, 2018)
This descriptive-correlational research determined the teachers’ competency in the use of ICT in teaching Physics and the students’ performance in Physics-8. Findings of the study revealed that: (1) The ICT competency level of the Grade-8 Physics Teachers is proficient. The teachers are in the basic level both in Pedagogy and Organization and Administration domains; (2) The ICT-based innovative practices performed by the teachers in teaching Physics which were categorized into three themes such as (1) lesson preparation, (2) lesson implementation, and (c) collaboration; (3) There is a moderate positive correlation that exists the between the teachers’ level of competency in the use of ICT and the students’ performance in Physics. The relationship is found to be significant; (4) The teachers perceived that the use of ICT; helped improve students’ understanding of science ideas, increases students’ motivation in learning science ideas, stimulates students’ interest to scientific ideas, facilitates the teaching and learning process, and provides teacher the opportunity to be innovative in delivering the lesson. The teachers also enumerated the top five most pressing challenges encountered that includes the following; poor/no internet connection, lack of seminars and trainings in ICT, lack of technical support, lack of time to plan and prepare lessons using ICT, and unavailability of ICT tools and software: and (5) An Enhancement Program entitled “ICT Competency Enhancement Program for Physics Teachers.” was proposed to address the advancement of the competency level of the teachers in the use of ICT for a more innovative teaching and learning process. Keywords: challenges in using ICT in teaching Physics, correlation students’ performance and teachers’ ICT competency, ICT competency enhancement program, Physics teachers using ICT, teachers’ ICT competency